New synergistic combinations of differentiation-inducing agents in the treatment of acute promyelocytic leukemia cells. (May 2018) - Amanzadeh, Amir; Molla-kazemiha, Vahid; Samani, Saeed; Habibi-Anbouhi, Mahdi; Azadmanesh, Kayhan; Abolhassani, Mohsen; Shokrgozar, Mohammad Ali
Highlights: Anti-CD44 monoclonal antibody improves "ATRA-FICZ"-induced APL (LSCs) cell differentiation. The "ATRA-FICZ-anti CD44 mAb" showed a synergistic effect in blocking CD44 antigen and triggering the maturation of NB4 cells. The highest anti-tumor activity of "ATRA-FICZ-anti CD44 mAb" was at 10 μg/ml of anti CD44 mAb in the triple combination. This triple compound may lead to novel clinical applications for APL and even other types of leukemia. Abstract: Acute promyelocytic leukemia (APL) was considered to be one of the most lethal forms of leukemia in adults before the introduction of the vitamin A metabolite all-trans retinoic acid (ATRA). Surprisingly, it has been confirmed that FICZ (6-Formylindolo (3, 2-b) carbazole) enhances ATRA-induced differentiation. Moreover, a number of studies have demonstrated that anti CD44 monoclonal antibody (mAb) induces to bring back differentiation blockage the leukemic stem cells. The level of differentiation markers including CD11b and CD11c in NB4 cells was assessed by flow cytometry. The induction of apoptosis was also evaluated. We estimated the induction potential of a triple compound of ATRA-FICZ, anti-CD44 maps. The cells showed the gradually increased expression levels of CD11b and CD11c. A mixture of a "CD44 mAb, ATRA and FICZ effectively promoted granulocytic maturation resulting in increased rates of apoptosis. The differences in expression of CD11b and CD11c at 5 μg/ml and 10 μg/ml were significant. These phenomena were highest at 10 μg/ml CD44 mAb concentrations. Synergistic induction differentiation and apoptosis of APL cells by using a co-treatment with novel triple compound are more effective for eradicating blasts and controlling the metastasis. Our results show that the addition of anti-CD44 mAb improves "ATRA-FICZ"-induced differentiation and has potential to reduce usual chemotherapy based treatments. Taken together, this compound may lead to novel clinical applications of differentiation-based approaches for APL and other types of leukemia. Further clinical studies would be recommended to clarify the clinical efficacy.